Epistemic Values in Indonesian Language Classroom Interactions: An Analysis of Lecturer Speech Acts at a Politeknik Ganesha Medan - Afri, Evan; Manugeren, M.; Barus, Efendi (International Journal of Multidisciplinary Sciences and Arts, 2026)
This study investigates the realization of epistemic values in Indonesian language classroom interactions, focusing on how lecturers at Politeknik Ganesha Medan employ speech acts to construct and negotiate knowledge during the teaching process. Adopting a qualitative descriptive approach, the research collected naturally occurring classroom data through observation, recording, and transcription. The analysis draws on Searle’s (1979) speech act theory integrated with an epistemic stance framework to explore how linguistic choices reflect epistemic positioning. The findings reveal that lecturers predominantly use assertive and directive speech acts to deliver information, guide reasoning, and confirm students’ understanding. These speech acts embody epistemic values such as authority, justification, evidence, and shared knowledge construction. Furthermore, the study identifies the use of evidential markers, modal verbs, and hedging devices that indicate varying degrees of certainty and epistemic responsibility. Such linguistic strategies help lecturers manage interpersonal relations, sustain engagement, and promote dialogic learning environments. The study concludes that epistemic values play a crucial role in shaping the quality of interaction and meaning-making in the classroom. Overall, this research contributes to educational linguistics and discourse analysis by demonstrating how epistemic meaning is enacted and negotiated in lecturer discourse within Indonesian tertiary education contexts.